2005
DOI: 10.1016/j.jpainsymman.2005.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility and Stability of Dexamethasone Sodium Phosphate and Ketamine Hydrochloride Subcutaneous Infusions in Polypropylene Syringes

Abstract: The stability of ketamine hydrochloride injection and dexamethasone sodium phosphate injection, when mixed and stored in polypropylene syringes, was studied. Formulations containing ketamine hydrochloride (50 mg or 600 mg) and dexamethasone sodium phosphate (1 mg) in 0.9% sodium chloride injection (to 14 ml) were prepared and stored at 4 degrees C, 23 degrees C, and 37 degrees C, under normal fluorescent light conditions, for 192 hours. The concentrations of the drugs were determined at 0, 2, 4, 8, 24, 48, 96,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…It is stable for 8 days when combined with ketamine hydrochloride, hydromorphone, metoclopramide and ranitidine http://www.palliative.org. (13) but precipitates, at certain concentrations, with midazolam hydrochloride (5), morphine hydrochloride (14) and haloperidol lactate (15) due to pH modifications. In our study pH modification did not affect drug stability.…”
Section: Resultsmentioning
confidence: 99%
“…It is stable for 8 days when combined with ketamine hydrochloride, hydromorphone, metoclopramide and ranitidine http://www.palliative.org. (13) but precipitates, at certain concentrations, with midazolam hydrochloride (5), morphine hydrochloride (14) and haloperidol lactate (15) due to pH modifications. In our study pH modification did not affect drug stability.…”
Section: Resultsmentioning
confidence: 99%
“…As for ketamine hydrochloride, the stability and compatibility test of ketamine hydrochloride combined with other drugs in infusion solutions has been widely demonstrated that ketamine hydrochloride is a highly stable drug. It has been reported to be stable with tramadol hydrochloride,25 morphine hydrochloride,2629 hydromorphone,30,31 fentanyl citrate,32 dexamethasone sodium phosphate,33 clonidine hydrochloride,34 midazolam hydrochloride,34 lormetazepam,34 and propofol35 in binary admixtures. Regarding droperidol, the solubility showed strong pH dependence (pKa was 7.64), which is stable in acid solution and may cause drug precipitation or crystallization in alkaline solution.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine hydrochloride was found to be compatible when diluted with water or 0.9% sodium chloride injection, packaging in glass vials, or polypropylene syringes at room temperature [ 34 – 36 ]. The compatibility and stability studies also reported that most of the tested drugs, such as morphine [ 37 40 ], hydromorphone [ 41 , 42 ], fentanyl citrate [ 43 ], and dexamethasone sodium phosphate [ 44 ], were stable and compatible in the presence of ketamine hydrochloride. Unfortunately, no published information is available on the compatibility and stability of butorphanol in combination with ketamine in PCA solution.…”
Section: Discussionmentioning
confidence: 99%